IOT ARCHITECTURE FOR AGRICULTURE APPLICATIONS: A FORMAL ASSESMENT - C.V. , Pallavi; Usha, S.; Balaji , S.; Tiwari, Harshvardhan (The journal of contemporary issues in business and government, 2021)
We are into the era where each individual, each device and each object is getting connected through the magical technology called “The Internet of things” on a scale that is inconceivable and it has turned out to be the popular innovation in the present situation. IoT empowers us to detect the physical medium to get to the information and transmit it by using the proper communication technology by interconnecting the detecting medium and the applications. IoT has numerous applications in every domain. Agriculture is one such domain. In this paper, we will look at farming applications from an IoT point of view and how fundamentally the impact of IoT can change the manner in which we do farming. Before structuring any of the IoT applications, it is especially required to have a short comprehension of the compositional perspective on the IoT architecture. In this paper, we have tried to explain diverse IoT architectures. Then towards the end, we have discussed an architecture that is appropriate unique for agriculture. We have, likewise, examined the interfacing technologies, challenges and applications for agricultureas considered from the IoT perspective.